2021
DOI: 10.1145/3449223
|View full text |Cite
|
Sign up to set email alerts
|

Designing for Independence for People with Visual Impairments

Abstract: The notion of "independence'' is frequently used to motivate technology design in the HCI sub-field of accessible and assistive technology for people with disabilities. Despite the term's pervasive use, the literature lacks a recent articulation of its meaning in the context of assistive technology. What does independence really mean? Scoping the study to people with visual impairments (PVI), we posed this question to 10 individuals from diverse backgrounds through in-depth, semi-structured interviews. Our fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Research with users with diferent sensory disabilities has found that well-functioning assistive technologies enable greater feelings of independence and self-eicacy [40,65]. However, research has also identiied bystanders' misperceptions of assistive technologies, which include beliefs that assistive technologies eliminate someone's disability, or that users with disability cannot do anything without their assistive technologies [64].…”
Section: Social Accessibilitymentioning
confidence: 99%
“…Research with users with diferent sensory disabilities has found that well-functioning assistive technologies enable greater feelings of independence and self-eicacy [40,65]. However, research has also identiied bystanders' misperceptions of assistive technologies, which include beliefs that assistive technologies eliminate someone's disability, or that users with disability cannot do anything without their assistive technologies [64].…”
Section: Social Accessibilitymentioning
confidence: 99%
“…A visually impaired researcher conducted a study on software capable of 3D modeling and 3D printing [31], reflecting an increasing demand for technology empowering direct interaction with CAD systems. Furthermore, independent creation not only fosters collaboration, democratizes creativity, and facilitates learning [32][33][34], but also underscores the importance of accessible CAD tools for boosting confidence, independence, and overall quality of life [35].…”
Section: Introductionmentioning
confidence: 99%